In Situ TiC/TiB2 Particulate Locally Reinforced Steel Matrix Composites Fabricated Via the SHS Reaction of Ni-Ti-B4C System - Yang, Ya-Feng; Wang, Hui-Yuan; Zhao, Ru-Yi; Liang, Yun-Hong; Jiang, Qi-Chuan (International journal of applied ceramic technology, 2009)
The composites synthesized with three kinds of B4C particles mainly consist of TiC, TiB2, and the alloy austenite containing Ni element. Ceramic particulate sizes in the composites synthesized with ∼3.5 and ∼45 μm B4C particles are larger than that synthesized with ∼140 μm B4C particle. No pores are found between the reinforcing region and matrix in the composites synthesized with ∼3.5 and ∼45 μm B4C particles, while some large pores exist in the composites synthesized with ∼140 μm B4C particle. With the decrease of B4C particle size, the pores in the composites become fewer and the hardness and wear resistance of the composites increase.